Cinnamaldehyde Improves Metabolic Functions in Streptozotocin-Induced Diabetic Mice by Regulating Gut Microbiota - Zhao H; Wu H; Duan M; Liu R; Zhu Q; Zhang K; Wang L (Dove Medical Press, 2021)
Honglei Zhao,1 Hongyan Wu,2 Meitao Duan,2 Ruixuan Liu,2 Quanhong Zhu,1 Kai Zhang,2 Lili Wang1 1Fuwai Hospital, Chinese Academy of Medical Sciences, Shenzhen, People’s Republic of China; 2Research Center for Biomedical Information Technology, Shenzhen Institutes of Advanced Technologies, Chinese Academy of Sciences, Shenzhen, People’s Republic of ChinaCorrespondence: Kai ZhangResearch Center for Biomedical Information Technology, Shenzhen Institutes of Advanced Technologies, Chinese Academy of Sciences, Shenzhen, People’s Republic of ChinaTel +86-13076878540Email kai.zhang@siat.ac.cnLili WangFuwai Hospital, Chinese Academy of Medical Sciences, Shenzhen, People’s Republic of ChinaEmail 1248532808@qq.comPurpose: The aim of the present study was to examine the protective effects of cinnamaldehyde (CA) on type 1 diabetes mellitus (T1DM) and explore the underlying molecular mechanisms by using multiple omics technology.Methods: T1DM was induced by streptozotocin in the mice. Immunostaining was performed to evaluate glycogen synthesis in the liver and morphological changes in the heart. Gut microbiota was analyzed using 16S rRNA gene amplification sequencing. The serum metabolomics were determined by liquid chromatography–mass spectrometry. The relevant gene expression levels were determined by quantitative real-time PCR.Results: CA treatment significantly improved the glucose metabolism and insulin sensitivity in T1DM mice. CA increased glycogen synthesis in the liver and protected myocardial injury in T1DM mice. CA affected the gut microbiota particularly by increasing the relative abundance of Lactobacillus johnsonii and decreasing the relative abundance of Lactobacillus murinus in T1DM mice. The glucose level was positively correlated with 88 functional pathways of gut microbiota and negatively correlated with 2 functional pathways of gut microbiota. Insulin resistance was positively correlated with 11 functional pathways. The analysis of serum metabolomics showed that CA treatment significantly increased the levels of taurochenodeoxycholic acid, tauroursodeoxycholic acid, tauro-α-muricholic acid and tauro-β-muricholic acid, taurodeoxycholic acid, taurocholic acid and taurohyodeoxycholic acid in T1DM mice. Taurohyodeoxycholic acid level was highly correlated with the blood glucose levels. Furthermore, the abundance of Faecalibacterium prausnitzii was positively correlated with AKT2, insulin like growth factor 1 receptor, E2F1 and insulin receptor substrate 1 mRNA expression levels, while taurohyodeoxycholic acid level was negatively correlated with IRS1 mRNA expression level.Conclusion: Our results indicated that CA may interfere with gut microbiota to affect host metabolomics, especially the bile acids, so as to directly or indirectly modulate the expression levels of glucose metabolism-related genes, thus subsequently reducing the blood glucose level in the T1DM mice.Keywords: cinnamaldehyde, type 1 diabetes, glucose, insulin, gut microbiota, serum metabolomics